STANDARDISASI BAHAN TAYANG BERKELANJUTAN MENUJU PEMBELAJARAN YANG BERKUALITAS DI PPSDM KEMENDAGRI REGIONAL YOGYAKARTA - Astuti, Widi (Journal of Innovation Research and Knowledge, 2026)
This study aims to identify the quality of presentation materials used by widyaiswara (trainers) at PPSDM Kemendagri Regional Yogyakarta, analyze the factors contributing to the low quality of these materials, and design an effective, efficient, and participant-oriented standard model for presentation materials. The research employed a mixed-method approach (quantitative and qualitative) through document analysis, questionnaires, interviews, and observations. Primary data were obtained from the analysis of presentation materials used in Latsar CPNS, PKP, and PKA training programs, as well as from alumni and widyaiswara questionnaires, while secondary data were collected from widyaiswara of other training institutions across the Yogyakarta region and interviews with institutional leaders. The proposed standard model for presentation materials includes four main aspects (content, presentation, language, and graphics), relevance to the curriculum and participants’ needs, efficiency in delivery time, and the support of a centralized digital storage system. The findings emphasize the urgency of implementing sustainable standardization of presentation materials to ensure quality consistency, relevance, and content updates, thereby supporting high-quality learning within PPSDM Kemendagri Regional Yogyakarta